The relationship between ornamental and managerial leaders in the private university sector: who runs the show and makes a difference? - Alam, Gazi Mahabubul; Asimiran, Soaib; Ismail, Ismi Arif Bin; Ahmad, Nor Aniza (SAGE Publications Inc., 2022)
Using school management settings, this manuscript developed important substantial leadership models such as “instructional,” “constructive,” and “distributed.” University leadership and especially in the private sector is an understudied topic. While private universities need to generate revenue for profits and survival, they should, at the same time, retain sound education philosophies, an extremely difficult task. Studies are yet to be conducted to understand how leaders of private universities handle this challenge, and this issue motivates the present research. Using Bangladesh as a case study, this qualitative study discovers that the “visionary” leadership approach is mainly used for business management models that govern private sector universities. This does not enable an established education leadership model to function well, if at all. This poses a serious challenge to educational philosophy. Innovation of a specialized private sector university leadership model is therefore required.